2021
DOI: 10.3390/genes12020163
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on the Origin of DNA Double-Strand Breaks and Its Implications for Ageing

Abstract: It is estimated that 10–50 DNA double-strand breaks (DSBs) occur in a nucleated human cell per cell cycle. We reviewed the present state of knowledge and hypothesized that the currently accepted mechanisms cannot explain such high frequency of DSBs occurring daily under normal physiological conditions. We propose an alternative model that implicates illegitimate genomic integration into healthy cells of cell-free chromatin (cfCh) particles released from the billions of cells that die in the body every day. Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…For example, cfChPs can readily enter into the healthy cells to damage their DNA, activate inflammatory cytokines and promote apoptosis via the mitochondrial pathway [13, 14]. Given that 1X10 9 -1X10 12 cells die in the body every day [56, 57], we have hypothesised that repeated and lifelong assault on healthy cells by cfChPs derived from the dying cells might be the underlying cause of ageing [15, 16]. In support of this hypothesis we show in this article that prolonged oral administration of R-Cu to ageing mice down-regulated multiple biological hallmarks of ageing and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cfChPs can readily enter into the healthy cells to damage their DNA, activate inflammatory cytokines and promote apoptosis via the mitochondrial pathway [13, 14]. Given that 1X10 9 -1X10 12 cells die in the body every day [56, 57], we have hypothesised that repeated and lifelong assault on healthy cells by cfChPs derived from the dying cells might be the underlying cause of ageing [15, 16]. In support of this hypothesis we show in this article that prolonged oral administration of R-Cu to ageing mice down-regulated multiple biological hallmarks of ageing and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we have reported that cell-free chromatin particles (cfChPs) that are released from the billions of cells that die in the body every day, and enter into the extracellular compartments of the body, can be readily internalised by healthy cells wherein they inflict dsDNA breaks, activate apoptotic pathways and induce inflammatory cytokines [13, 14]. This has led us to hypothesise that repeated lifelong assault on healthy cells by cfChPs may be the underlying cause of ageing [15, 16]. Our group has successfully isolated and characterised cfChPs from human serum, which upon EM examination revealed extensive size heterogeneity ranging between ∼10nm and ∼1000nm [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cell-free chromatin (cfCh) particles that are released from the billions of cells that die in the body everyday can integrate into genomes of healthy cells to trigger dsDNA breaks, apoptosis and activation of inflammatory cytokines [5,6]. We have hypothesized that repeated genomic integration of cfCh particles occurring throughout life may be the underlying cause of ageing and degenerative disorders [7,8]. We have previously reported that toxicity of chemotherapy is largely not due to the direct effects of the drugs themselves; rather it is mainly due to DNA damage, apoptosis and hyper-inflammation triggered by cell-free chromatin particles that are released because of drug induced host cell death [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have reported that cell-free chromatin particles (cfChPs) that are released from the billions of cells that die in the body every day, and enter into the extracellular compartments of the body, can be readily internalised by healthy cells wherein they inflict dsDNA breaks, activate apoptotic pathways and induce inflammatory cytokines 13 , 14 . This has led us to hypothesise that repeated lifelong assault on healthy cells by cfChPs may be the underlying cause of ageing 15 , 16 . Our group has successfully isolated and characterised cfChPs from human serum, which upon EM examination revealed extensive size heterogeneity ranging between ~ 10 and ~ 1000 nm 13 .…”
Section: Introductionmentioning
confidence: 99%